Konzeption, Realisierung und Verifikation eines automobilen Forschungsscheinwerfers auf Basis von Digitalprojektoren - Michenfelder, Steffen (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2014)
As far as automotive lighting technoligies are concerned, the question rises in which way different technologies nowadays and in future can be displayed realistically and with high validity while simultaneously saving costs and time. This paper describes the conception and the technical installation of the multifunctional headlighting platform Propix which is supposed to being used for various research activity in the field of automotive lighting physiology.